Dukungan Pimpinan dan Dampaknya Terhadap Perilaku Kerja Proaktif yang Dimediasi oleh Budaya Kerja (Studi pada PT. PLN (Persero) Unit Layanan Pelanggan (ULP) Muara Sabak) - Sutopo, Tri; Amin, Shofia; Indrawijaya, Sigit (Universitas Batanghari Jambi, 2024)
This research aims to describe leadership support, work culture and proactive work behavior at PT. PLN (Persero) Muara Sabak Customer Service Unit (ULP), as well as testing the influence of leadership support on proactive work behavior, both directly and indirectly, work culture. The population in this study were employees at PT. PLN (Persero) ULP Muara Sabak, totaling 60 employees. Meanwhile, to determine the sample in this research, the census technique was used. The research uses a quantitative approach with survey methods and uses Partial Least Square (PLS) data analysis. The research results show that the support from the leadership of PT. PLN (Persero) ULP Muara Sabak directly or indirectly through work culture has a significant influence on employee proactive work behavior. These results indicate that strong leadership support creates a work culture so that employees can adapt and behave proactively in facing challenges.